Comparison of »Slavic« Pots with Gender and Age of the Deceased Primerjava prostornine “slovanskih” loncev s starostjo in spolom pokojnika v grobu - Žorž, Alja (Studia mythologica Slavica, 2007)
Within this study I have attempted to determine whether, in Early medieval contexts, we can or cannot trace any links between size of a pot and both gender and age of the deceased. Have Slav people offered pots within graves of their ancestors, and did these pots carry a certain magical message, maybe as a status symbol? Or does the pot rest near the deceased merely from the point of view of use in everyday life, as a private property of the dead, which he will take to »the other side«? With the results of analysis of the volume of the pots I have answered only a few questions, but guessings, which point out interesting inhumation practices of this time, have appeared. In any case, Slavic pots, in the sense of grave offerings, did certainly have a sort of symbolic meaning.